Ciclos político-econômicos nos estados brasileiros: uma análise do gasto público através de dados em painel espacial de 2003 a 2014 - Puchale, Caroline Lucion (2019)
Traditional economic theory has established that fluctuations in the economy are motivated only by economic phenomena. However, through the works developed by Kalecki (1943) and Downs (1957) it is said that particular attitudes of rulers are also factors responsible for the oscillations in the economy. From 1970 onwards, the work of Nordhaus (1975), Hibbs (1977), Alesina (1987), Rogoff and Siebert (1988), Rogoff (1990) and Persson and Tabellini (1990) discuss the interaction between the economic and political aspects begins to gain formalization being called Political-Economic Cycles (CPE). This theory is based on the assumption that rulers have particular desires of prestige and power, and this particular desire is the guide to their decision-making. The CPE is divided into two main models, one concerning the electoral cycle and the other about party cycles. Electoral cycles are formed when there is an effort on the part of policymakers to carry out measures that please the voter, thereby aiming at electoral bargaining (FIALHO, 1999). Therefore, in the run-up to the elections there is an increase in the levels of public spending to carry out measures of easy electoral visualization. Party cycles are characterized by the relation between public expenditure and its ideological bias. Leftist parties are likely to hold higher levels of public spending, since they cherish social welfare. However, right-wing parties are more conservative and prefer stabilized inflationary levels (HIBBS, 1977; ALESINA, 1987). In this discussion, there is still another bias that becomes instigating: spatial inclinations in voter decision-making. It is reinforced in this literature that the candidates are based on the pattern of public spending executed by neighboring regions because they know that the voters observe the actions performed by public agents of border regions in order to decide their vote. Therefore, the main objective of this study is to detect possible influences of the opportunist and partisan cycles in the oscillations of the total public expenditures and by budgetary function, health and sanitation, education and cultural and investments of the twenty six Brazilian states and the federal district in the period of 2003 to 2014, taking into account the spatial aspect. In order to reach this end the method used was the econometric of data in space panel. As main results, the presence of opportunist political-economic cycles was observed in a soft way, since it was concentrated only in the investment accounts. Issues related to party political alignment and re-election phenomena were also investigated and it became clear that alignment is an important tool to increase the ease of raising public spending. Regarding the reelection phenomenon, it was found that policymakers, when in the last term, are prone to generate public deficits. In the analysis of party cycles, the same was observed in expenditure on health/sanitation, education/culture and total expenditure. Regarding geographic variables in party cycle models, the yardstick competition effect is present. Demonstrating that the electoral aspect transcends the borders of states.